Whale rider [videorecording (DVD)] - Caro, Niki, 1967-; Castle-Hughes, Keisha, 1990-; Paratene, Rawiri; Haughton, Vicky; Curtis, Cliff, 1968-; Ihimaera, Witi, 1944- (Columbia TriStar Home Entertainment, 2003)
The Whangara people believe their ancestor Paikea was saved from drowning by riding home on the back of a whale. The tribal group has since granted leadership positions to the first-born males, believing them to be descendants of Paikea. But then a young mother dies in childbirth along with her newborn male son. His twin sister survives and the little girl, Pai, is brought up by her grandparents. Learning the skills of chiefdom from her uncle, Pai shows that she possess a natural leadership ability.